Goji Who? Morphological and DNA Based Authentication of a “Superfood” - Wetters, Sascha; Horn, Thomas; Nick, Peter (Frontiers in Plant Science, 2018)
“Goji” (Lycium barbarum and Lycium chinense) is a generic name for medical plants with a long historical background in the Traditional Chinese Medicine. With the emerging trend of „Superfoods“ several years ago, Goji berries soon became an established product in European countries and not only are the most popular product of Traditional Chinese Medicine outside of China but to this day one of the symbols of the entire „Superfood“ trend. However, since Goji is an umbrella term for different plant species that are closely related, mislabeling and adulterations (unconsciously or purposely) are possible. We carefully verified the identity of Goji reference plant material based on morphological traits, mainly floral structures of several inflorescences of each individual, in order to create a robust background for the downstream applications that were used on those reference plants and additionally on commercial Goji products. We report morphological and molecular based strategies for the differentiation of Lycium barbarum and Lycium chinense. The two different Goji species vary significantly in seed size, with an almost double average seed area size in Lycium chinense compared to Lycium barbarum. Differences could be traced on the molecular level as well; using the psbA-trnH barcoding marker, we detected a single nucleotide substitution that was used to develop an easy one-step differentiation tool based on ARMS (Amplification refractory mutation system). Two diagnostic primers used in distinct multiplex PCRs yield a second diagnostic band in a subsequent gel electrophoresis for Lycium barbarum or Lycium chinense, respectively. Because of the innate positive control the ARMS approach is a strong but simple tool to trace either of the two different Goji species. Both the morphological and the molecular analysis showed that all of the tested commercial Goji products contained the species Lycium barbarum var. barbarum, leading to the assumption that consumer protection is satisfactory.